Test of VNN Virus Resistance In Several Economic Fish Species - Betutu Senggagau (JURNAL PERIKANAN DAN KELAUTAN, 2011)
VNN or Viral Nervous Necrosis is one of dangerous pathogen which might could infects some marine fishes.This virus has various type of resistance level to different marine fish. An attempt to test the fishes which have highest level of resistance for VNN virus have been conducted. About 0.1 ml of VNN virus extract were injected to seven economic fish species. Prior the treatment, all fishes were tested using the PCR technique. The data were analysed by variance of randomized block design consisted of treatments and control. The results showed that the VNN virus injection to the fish group have significant impact at 1% level. Results of challenge test showed that Silver Pompanos have the strongest resistance against VNN virus compared to the other species with 90% of survival rate , while the PCR test showed no esophageal VNN. While the Humpback groupers have the weakest resistance with 20% of survival rate with PCR test showed that VNN infection have severe stages.